SUBDUCTED OCEANIC LITHOSPHERE AND THE ORIGIN OF THE 'HIGH μ' BASALT HELIUM ISOTOPIC SIGNATURE - Moreira M.; Kurz M.D. (My University, 2001)
The isotope geochemistry of ocean island basalts has been used to infer the presence of ancient recycled oceanic crust in the mantle. The helium isotopic ratios of basalts from HIMU sources, having high U/Pb (μ) and low Rb/Sr, are thought to be derived from recycled ocean crust, but are only slightly more radiogenic than average mid-ocean ridge basalt (MORB) values (i.e. 3He/4He of 6-7 R/Ra, compared to ~8 R/Ra). These values appear to be inconsistent with ancient recycled oceanic crustal sources because the helium should be significantly more radiogenic. We propose a simple model to explain this helium isotopic composition. The basic hypothesis is that the entire oceanic lithosphere is subducted, of which the oceanic crust is only a small fraction. Based on measurements from xenoliths, the residual lithosphere contains ~5x10-7 ccSTP/g of helium. The relatively low uranium content in the mantle lithosphere (<0.5 ppb) leads to 3He/4He ratios slightly more radiogenic than the upper mantle ratio after 2 Ga, and could be the source of the HIMU helium isotopic composition by mixing with the subducted oceanic crust. Although the helium content of the subducted lithosphere is highly uncertain, existing data suggest that a simple closed system evolution model can explain the helium isotopic composition of the HIMU mantle sources.
Keywords: HIMU; HELIUM; LITHOSPHERE